Reaching consensus on communication of critical laboratory results using a collective intelligence method - Llovet, Maria Isabel; Biosca, Carmen; Martínez-Iribarren, Alicia; Blanco, Aurora; Busquets, Glòria; Castro, María José; Llopis, Maria Antonia; Montesinos, Mercè; Minchinela, Joana; Perich, Carme; Prieto, Judith; Ruiz, Rosa; et al. (Clinical chemistry and laboratory medicine, 2018)
There is no consensus in the literature about what analytes or values should be informed as critical results and how they should be communicated. The main aim of this project is to establish consensual standards of critical results for the laboratories participating in the study. Among the project's secondary objectives, establishing consensual procedures for communication can be highlighted. Consensus was reached among all participating laboratories establishing the basis for the construction of the initial model put forward for consensus in conjunction with the clinicians. A real-time Delphi, methodology "health consensus" (HC), with motivating and participative questions was applied. The physician was expected to choose a numeric value within a scale designed for each analyte. The medians of critical results obtained represent the consensus on critical results for outpatient and inpatient care. Both in primary care and in hospital care a high degree of consensus was observed for critical values proposed in the analysis of creatinine, digoxin, phosphorus, glucose, international normalized ratio (INR), leukocytes, magnesium, neutrophils, chloride, sodium, calcium and lithium. For the rest of critical results the degree of consensus obtained was "medium high". The results obtained showed that in 72% of cases the consensual critical value coincided with the medians initially proposed by the laboratories. The real-time Delphi has allowed obtaining consensual standards for communication of critical results among the laboratories participating in the study, which can serve as a basis for other organizations.